A log cabin Christmas collection : 9 historical romances during American pioneer Christmases - Brunstetter, Wanda E. (Uhrichsville, Ohio : Barbour Pub., 2011)
Discover how rough-hewed shelters become a home in which faith, hope, and love can flourish. Marvel in the blessings of Christmas celebrations without the trappings of modern commercialism where the true meaning of the day shines through. And treasure this exclusive collection of nine Christmas romances penned by some of Christian fiction's best-selling authors.
Snow angel / Margaret Brownley -- The Christmas secret / Wanda E. Brunstetter -- Christmas traps and trimmings / Kelly Eileen Hake -- A star in the night / Liz Johnson -- The courting quilt / Jane Kirkpatrick -- Under his wings / Liz Tolsma -- The dogtrot Christmas / Michelle Ule -- A grand country Christmas / Debra Ullrick -- Christmas service / Erica Vetsch.
Keywords: Christmas stories; Frontier and pioneer life -- Fiction; Love stories; Historical fiction